ANALISIS PENGARUH PENGALAMAN KERJA, LINGKUNGAN KERJA, PENGHARGAAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI - Said, Akbar; Iskandar, Muh Resky (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
The study aims to determine and analyze the influence of Work Experience, Work Environment, Awards and Training on employee performance and which variables have the most influence on the Kalla Aspal Division at PT Bumi Sarana Utama Makassar. This type of research is quantitative research. Quantitative data is data that is managed by calculating or spreading it into numbers or values ​​related to employee performance. The analysis tool used in this study is multiple linear regression analysis to test whether there is a relationship or influence between the two independent variables (X) with or more dependent variables (Y). Based on the results of the study, it shows that the variables Work Experience, Work Environment, Awards, and training together have a significant influence on employee performance and have a very strong influence on employee performance. Partially, the variables Work Experience, Work Environment, Awards, and training have a positive and significant effect on employee performance at PT. Bumi Sarana Utama Makassar. The variable Work Experience partially has a dominant effect on employee performance at PT. Bumi Sarana Utama Makassar